Environmental performance of microalgae hydrothermal liquefaction: Life cycle assessment and improvement insights for a sustainable renewable diesel. (March 2022) - Marangon, B.B.; Castro, J.S.; Assemany, P.P.; Couto, E.A.; Calijuri, M.L.
Abstract: The potential environmental impacts of bio-oil production from algal biomass via hydrothermal liquefaction (HTL) and its upgrading in renewable diesel were obtained. The gate-to-gate boundary was applied to obtain 1 MJ of energy as the functional unit. Marine eutrophication was the most impacted category due to N emission from the aqueous phase. In other categories, the HTL process was more harmful to the environment due to heat demand, and bio-oil upgrading contributed to 79% of the environmental impacts in the climate change category. The sensitivity analysis highlighted the importance of the residual heat recovery in the HTL reactor, indicating the potential to reduce up to 52% of impacts on marine ecotoxicity with a 10% increase in this parameter. Finally, a new scenario was proposed to reduce the heat input into the HTL reactor and recirculate the aqueous phase after dilution. Results demonstrated a 45% reduction in the potential environmental impacts and a 2x greater energy balance than the base scenario. In the new scenario was emitted 0.1349 kg of CO2 eq per MJ. In the damage assessment, the new scenario caused less damage than the base scenario, showing the benefits of the proposed improvements. When comparing the bio-oil from the new scenario with the conventional diesel, damage in the resource scarcity category was decreased by 6x. The environmental sustainability of microalgae biotechnology for bio-oil obtention through HTL still has to be improved, especially concerning subproducts valorization and heat recovery in the reaction. Graphical abstract: Image 1 Highlights: The environment was under severe pressure due to the release of the aqueous phase in the water. The hydrothermal liquefaction of biomass impacted more than the upgrading of bio-oil. Optimizing the residual heat recovery in the reactor reduces harmful environmental impacts. The use of the aqueous phase can eliminate impacts on marine eutrophication.